Political institutions and the governmental burden on businesses - Weifeng Zhong; Ruiqing Zhong (American Enterprise Institute (AEI), 2018)
Businesses are "burdened" by government through corporate taxes and bureaucratic procedures. We interpret these two channels as tools for raising revenue and study, theoretically and empirically, how different political institutions rely on these tools. We establish two stylized facts: the degree of democracy has inverted-U relationships with both the bureaucratic and tax burdens. We match these facts with a dynamic political-economic model of fiscal policy where revenues are raised through the burden on businesses and the returns to public capital, and where the degree of democracy is modeled as the limit on the appropriation of capital by misbehaving politicians.
Keywords: A; 330; Regulation; corporate taxes; business; bureaucracy; institutions